2018
DOI: 10.1364/ao.57.004985
|View full text |Cite
|
Sign up to set email alerts
|

Elemental composition analysis of granite rocks using LIBS and LA-TOF-MS

Abstract: Qualitative and quantitative analysis of the raw granite rocks acquired from deposits in the Hunza district, Gilgit area of Pakistan were studied using laser-induced breakdown spectroscopy (LIBS) and laser ablation time-of-flight mass spectrometry (LA-TOF-MS). The optical emission spectra of the granite rocks used in artificial jewelry and for flooring tiles show the emission lines of (Si, Ca, K, Fe, Mg, Al, Na, and Li) and (Si, Ca, K, Fe, Mg, Al, Ti, Na, Ba, and Li), respectively. The mass spectra of these gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…It is evident from Table 5 that the percentage error between the measurements of CF-LIBS and XRF techniques range from almost 8% to 18% for major elements (Ti, W, Fe), whereas for minor and trace elements, relative error increases from 17% to 88%. These results are consistent with many previous studies suggesting that CF-LIBS performs almost equivalently well for quantifying major elements in a multi-elemental material, but its efficiency reduces for minor and trace element quantification [ 25 , 26 , 27 , 28 , 29 , 30 ]. However, the advantage of LIBS over XRF is the detection of lighter elements in multi-elemental complex materials.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It is evident from Table 5 that the percentage error between the measurements of CF-LIBS and XRF techniques range from almost 8% to 18% for major elements (Ti, W, Fe), whereas for minor and trace elements, relative error increases from 17% to 88%. These results are consistent with many previous studies suggesting that CF-LIBS performs almost equivalently well for quantifying major elements in a multi-elemental material, but its efficiency reduces for minor and trace element quantification [ 25 , 26 , 27 , 28 , 29 , 30 ]. However, the advantage of LIBS over XRF is the detection of lighter elements in multi-elemental complex materials.…”
Section: Discussionsupporting
confidence: 92%
“…This methodology is preferred over the calibration method because it eliminates the matrix effect and requires no reference sample. CF-LIBS technique has been successfully employed for compositional analysis of various types of ores and minerals such as quartz, limestone and granite gneiss [ 26 , 27 , 28 ]. Concentration of Cu along with other elements has been successfully measured using CF-LIBS method in copper-rich minerals such as malachite and chalcopyrite [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, the CF-LIBS method appears to be a suitable and effective alternative to the calibration method. In some previous studies, the CF-LIBS method was utilized for measurement of elemental composition of geological samples such as limestone, granite, malachite, and nephrite, and results were compared with standard techniques such as energy dispersive X-ray spectroscopy (EDX), X-ray fluorescence (XRF), and laser ablation-time of flight-mass spectrometer (LA-TOF-MS) [24][25][26]44,45]. In all of these studies, quantitative results obtained with CF-LIBS showed reasonable agreement with the standard analytical techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Malachite, a copper-bearing mineral, was also quantified using CF-LIBS methodology [25]. The same technique was adopted for the quantification of granite rock [26].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional detection methods, LIBS technique has the advantages of fast analysis speed, little sample preparation, and simultaneous analysis of multiple elements [21,25]. By analyzing the spectral signal emitted from laser plasma, LIBS has been widely used in the quantitative and qualitative analysis of plant materials [21,25,27,28,29], animal tissue [24,30], mineral resources [31,32], industrial application [33] and so on. The previous studies provide a basis for LIBS to be applied in the authenticity identification of Chinese medicine.…”
Section: Introductionmentioning
confidence: 99%